Intestinal infarction caused by carcinoid associated elastic vascular sclerosis: early presentation of a small ileal carcinoid tumour. Issue 5 (May 1989) - Harvey, J N; Denyer, M E; DaCosta, P
Abstract : We describe a patient with extensive ischaemic necrosis of the ileum as a result of elastic vascular sclerosis (EVS). A 2 cm carcinoid tumour was located nearby with microscopic evidence of spread to regional lymph nodes. Severe intestinal ischaemia caused by carcinoid associated EVS may be the presenting feature of small carcinoid tumours resulting in their early diagnosis.